PENINGKATAN KETERAMPILAN SANTRI DALAM MENGELOLA MEDIA DIGITAL DI PONDOK PESANTREN MIFTAHUL HUDA RAWALO BANYUMAS - Herdiana, Aan; Wakhyudi, Yukhsan; Hidayat, Imam Maarif; Alfaozi, Mahfud; Ramadhani, Angger Sulung; Noviyanti, Intan (Politeknik Perkeretaapian Indonesia Madiun, 2025)
This community service program is titled Improving Students' Skills in Managing Digital Media at Pondok Pesantren Miftahul Huda Rawalo Banyumas. The program aims to equip students with basic digital media management skills as a means of modern da'wah. Using the Participatory Action and Learning System (PALS) method, which fundamentally involves partners in active learning participation within the program, the focus is on the application of science and technology through digital media management skills at the pesantren. This program actively engaged students in activities such as socialization, training, and mentoring. The program began with an introduction to the importance of digital media as a medium for da'wah, followed by technical training on managing the pesantren's social media platforms. Based on the results of assessments conducted through pre-tests and post-tests, there was a 25% increase in students' awareness of the potential of da'wah through digital platforms. The activities culminated in the establishment of the pesantren's media platform. The sustainability of this community service program is realized through the formation and management of the pesantren's digital media, named